RELIGIOUS INDUSTRY IN HALAL FOOD CONSUMPTION - Havva SÜLÜN ERGÜL (Fırat University, 2019)
Religion has been considered as important reflection of social order throughout the ages. As primary social facts, religion and religious rituals have a great impact for those who choose to follow their faiths' dietary restrictions. The structure and the practices of these religious eating rules are almost same in all religions but their labeling or naming it differs from one religion to another. The appropriate ‘clean’ food is named halal in Islam and Kosher in Jewish laws. Parallel to creation of social fact with the concept of religion, this paper is mainly about the distribution and consumption of halal food in Turkey as one of the predominantly Muslim countries. By the help of comparison with kosher food and consumption and certification of halal food world widely, the paper aims to reach the conclusion that religious requirements has turned into industry and became a institutionalized power for the recent decades. With the help of sociology, the theory part of the topic will be discussed by exemplifying from sociologists arguments. And the practice of its theory in Turkish example will be stated with observed instances. Concentrating on the religious industrialization generally, I will talk about the function of halal concept as a sample. This topic is recent for Turkey and has the characteristics of a detailed thesis with more supportive scientific data in further researches.